Medical Students' Perceptions of the Clinical Reasoning in Large Classes at the Universitas Muhammadiyah Jakarta - Nabilla Aulia Maharani; Oktarina Oktarina (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2025)
Background: Clinical reasoning (CR) is essential for all doctors, enabling them to manage patient problems effectively. Poor CR ability can lead to medical errors. The medical study program at the Faculty of Medicine and Health, Universitas Muhammadiyah Jakarta (MP-UMJ), has introduced an innovative CR learning method, Clinical Reasoning in Large Class (CRILC). However, there is a lack of research on the perceptions of MP-UMJ students regarding this learning method. Therefore, this study aims to investigate and present the perceptions of MP-UMJ medical students regarding CRILC. Methods: This research used a mixed method with a concurrent study design. The research was conducted in October-November 2023 among students of the Medical Study Program, University of Muhammadiyah Jakarta. Secondary data obtained from the student questionnaire survey regarding the CRILC evaluation held by the lecturer in charge of the block is used in this research. A total of 100 sample answers were taken for analysis. Quantitative data was processed using SPSS and NVivo12 for the qualitative data. Results: The study revealed a positive perception among MP-UMJ medical students towards CRILC, highlighting its effectiveness and potential for broader adoption. Positive perception was obtained regarding students' impressions and benefits after participating in CRILC. Problem-Based Learning (PBL) is the method that most helps students participate in CRILC. Determining patient assessment is the most frequently experienced difficulty during CRILC. Most students think that the CRILC method has been implemented well. Conclusion: MP-UMJ medical students have a positive perception of the CRILC.